A study of professionalism during the Falklands/Malvinas War: The case of the Argentine Marines - Alejandro Luis Corbacho (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
This paper assesses how organizational culture affects the fighting performance of units in the battlefield. By focusing on the behavior of a group of Argentine troops during the Falklands War in 1982. Between May 21 and June 14, Argentine and British troops engaged in a fierce land battle for the possession of a group of islands in the South Atlantic known as the Falkland/Malvinas. In a campaign that a participant characterized as no picnic, British Marines, paratroopers, and Guards troops defeated the Argentine garrison comprised mainly of conscripted soldiers. However, Argentine Marine units especially distinguished themselves for their fighting ability. According to the author the main reason for this performance rests on their organizational culture.
Keywords: 330